Counterspace capabilities: Renewed hope for cooperative governance? - Almudena Azcárate Ortega; Victoria Samson (Centre for International Governance Innovation (CIGI), 2025)
Ever since humankind first launched objects into space, counterspace capabilities (also known as "space weapons") were developed to disrupt or destroy them. Now that space is increasingly being used for both civilian and military applications, space technologies have evolved to meet these needs, but regulations to protect space have lagged behind. This paper looks at how the international community is addressing the threats posed by these technologies through multilateral efforts and regulatory mechanisms to enhance space security.
Keywords: 330